Early Imitation Within a Functional Framework: The Importance of Person Identity, Movement, and Development - Meltzoff, Andrew N. (1992)
Facial imitation was investigated in infants 6 weeks and 2 to 3 months of age. Three findings emerged: (a) early imitation did not vary as a function of familiarity with the model—infants imitated a stranger as well as their own mothers; (b) infants imitated both static facial postures and dynamic facial gestures; and (c) there was no disappearance of facial imitation in the 2- to 3-month age range, contrary to previous reports. Two broad theoretical points are developed. First, a proposal is made about the social and psychological functions that early imitation serves in infants’ encounters with people. It is argued that infants deploy imitation to enrich their understanding of persons and actions and that early imitation is used for communicative purposes. Second, a theoretical bridge is formed between early imitation and the “object concept.” The bridge is formed by considering the fundamental role that identity plays in infants’ understanding of people and things. One of the psychological functions that early imitation subserves is to identify people. Infants use the nonverbal behavior of people as an identifier of who they are and use imitation as a means of verifying this identity. Data and theory are adduced in favor of viewing early imitation as an act of social cognition.